Urgensi Pembelajaran Ushul Fiqih dalam Menanamkan Sikap Moderat Siswa - Zainuddin; Sapiuddin Shidiq; Abdul Ghofur (Qiro'ah : Jurnal Pendidikan Agama Islam, 2021)
This study aims to explore the urgency of learning ushul fiqh in instilling moderate attitudes in students at Madrasah Mu'allimin Ad Diniyyah Al Hikmah 1 Brebes. This research is a field research that uses qualitative methods with a case study approach. research oriented to finding natural symptoms, collecting data through observation, interviews and documentation that support research. The results of this study are ushul fiqh learning in instilling moderate attitudes to students, it can be taken through the first through content, the second method of active learning. Third, habituation activities, Fourth, is the evaluation of coaching and guidance. Characteristics of students' moderate attitude through learning ushul fiqh 1) Tasamuh or tolerance, respect for differences. 2) Islah or reform is an attitude of reviewing a law in the future. 3) I'tidal or just. 4) tawazun or balance between understanding aqli reasoning and manhaji reasoning. 5) Civilized tahaddur is a noble character. 6) Shura or deliberation. 7) Alawiyah or priority. 8) Tatawwur wa Ibtikar is innovative and dynamic. This shows that ushul fiqh learning has an important role in instilling a moderate attitude in students